تقييم دور الرقابة الشرعية بالمصارف الإسلامية الليبية "دراسة تطبيقية بمصرفي اليقين والأندلس" (Comprehensive Journal of Science, 2025)
The study aimed to evaluate the reality of Sharia supervision within the Al-Yaqeen and Al-Andalus Banks and to identify the extent of the effectiveness of the Sharia supervision work in enhancing and developing the Sharia supervision work in a way that supports the effectiveness of the work of Islamic banks to carry out their role effectively. The study relied on the descriptive analytical approach, and the sample of the study represents the employees of the Al-Yaqeen and Al-Andalus Banks. In the city of Tripoli, the questionnaire was used to collect data. 150 questionnaires were distributed, including 97 questionnaires for Al-Yaqeen Bank and 53 questionnaires for Al-Andalus Bank. 113 questionnaires were retrieved, including 77 for Al-Yaqeen Bank and 36 for Al-Andalus Bank, i.e. copies retrieved at a rate of 75.33%. The role of Sharia supervision was evaluated from five aspects: adequacy and efficiency. Those working in Sharia supervision, disclosure and transparency, the role of Sharia supervision in spreading the culture of Islamic banking, advice and guidance, the comprehensiveness of Sharia supervision work, the automation of Sharia supervision work, and the data was analyzed using the Statistical Package for the Social Sciences (SPSS) program, version twenty-four. Through statistical tests, Cronbach’s alpha test, proportional distribution, Wilcoxon test about the mean, and Z test about the mean, with a confidence level of 95%, several results were reached, the most important of which are: the lack of qualified and specialists in Islamic finance and the jurisprudence of transactions, and the lack of a sufficient number of Sharia auditors within the study banks, as well as the sufficiency of The report of the Sharia Supervisory Board presented to the General Assembly expresses a general opinion on the Sharia soundness of the bank’s business without clarifying the Sharia violations that occurred. It also revealed the weakness of the role of supervision in spreading the culture of Islamic banking, advice and guidance. The Sharia supervision in Al-Andalus Bank is considered to be more efficient and effective than that of Al-Yaqin Bank, and recommended The study aims to provide a sufficient number of qualified Sharia auditors who are familiar with accounting aspects and Sharia controls, and to achieve integration between internal and external Sharia audit to ensure the achievement of the audit objectives in detecting and correcting violations and accuracy in assessing the risks of Sharia non-compliance. It recommends developing the expertise and skills of employees through seminars and training courses and developing a program. Awareness through various media to introduce the importance of Islamic banking. It requires the Authority to provide advice and guidance in order to diversify investments and activate Islamic financing formulas and not be limited to the Murabaha formula. AlYaqeen Bank and Andalus Bank should make more efforts to improve the quality and effectiveness of the Sharia supervision work within the bank..